The Living Eye “Disarms” Uncommitted Autoreactive T Cells by Converting Them to FoxP3(+) Regulatory Cells Following Local Antigen Recognition - Zhou, Ru (2012)
Immune privilege is used by the eye, brain, reproductive organs and gut to preserve structural and functional integrity in the face of inflammation. The eye is arguably the most vulnerable, and therefore also the most “privileged” of tissues, but paradoxically, remains subject to destructive autoimmunity. It has been proposed, although never proven in vivo, that the eye can induce T regulatory cells (Tregs) locally. Using FoxP3-GFP reporter mice expressing a retina-specific T cell receptor, we now show that uncommitted T cells rapidly convert in the living eye to FoxP3(+) Tregs in a process involving retinal antigen recognition, de novo FoxP3 induction and proliferation. This takes place within the ocular tissue and is supported by retinoic acid, which is normally present in the eye due to its function in the chemistry of vision. Non-converted T cells showed evidence of priming, but appeared restricted from expressing effector function in the eye. Preexisting ocular inflammation impeded conversion of uncommitted T cells into Tregs. Importantly, retina-specific T cells primed in vivo before introduction into the eye were resistant to Treg conversion in the ocular environment, and instead caused severe uveitis. Thus, uncommitted T cells can be disarmed, but immune privilege is unable to protect from uveitogenic T cells that have acquired effector function prior to entering the eye. These findings shed new light on the phenomenon of immune privilege and on its role, as well as its limitations, in actively controlling immune responses in the tissue.